Invariant algebras and geometric reasoning - Li, Hongbo (World Scientific Publishing Co. Pte. Ltd, 2008)
The demand for more reliable geometric computing in robotics, computer vision and graphics has revitalized many venerable algebraic subjects in mathematics — among them, Grassmann–Cayley algebra and Geometric Algebra. Nowadays, they are used as powerful languages for projective, Euclidean and other classical geometries.